Neglected ocular surface care in critical care medicine: An observational study. Issue 4 (August 2020) - Selvan, Harathy; Pujari, Amar; Sachan, Anusha; Gupta, Shikha; Sharma, Namrata
Highlights: Ocular surface disorders (OSD) have been observed in nearly 60% of critically ill patients. The eye is more often looked at as a diagnostic aid, and the return reward of care has not been reciprocal. A simple test of observing torch light reflection from the cornea can help pick up early signs of exposure keratopathy. Optimal eye care in unconscious patients can avert development of exposure-related complications and subsequent ocular morbidity. Abstract: Aim: To study the prevalence of lagophthalmos and its related complications among the unconscious patients admitted in the intensive care units (ICU)/wards of a tertiary care centre. Methods: Cross-sectional observational study. Results: A total of 87 unconscious patients were included. 44 were children and 43 were adults. The overall median age of patients was 16 years (range: 9 days- 85 years). 53/87 (60.91%) showed signs of lagophthalmos, among which 56.60% (30/53) were children and 43.40% (23/53) were adults. There was no significant difference in the exposure patterns between children and adults (p = 0.25). Exposure related manifestations (conjunctival/corneal) were found in 49/87 patients (56.32%). The most common conjunctival manifestation was chemosis, occurring in 28/53 patients (52.83%). Corneal exposure was seen in 31/53 patients (58.49%), of which fragile epithelium was the commonest finding (32.08%). Only 17/31 (54.83%) cornea exposed eyes were taped, of which 15 were sub-optimal. 6 patients were unnecessarily taped. Signs of infection were noted in 8/53 eyes (15.09%). Conclusion: Optimal eye care in unconscious patients can avert the development of exposure-related complications and subsequent ocular morbidity. Adoption and implementation of systematic protocols can help improve the standard of care.